2007
DOI: 10.1186/ar2175
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation end products Glycine 82 Serine polymorphism and risk of cardiovascular events in rheumatoid arthritis

Abstract: Patients with rheumatoid arthritis (RA) are at risk of excess mortality, predominantly owing to cardiovascular (CV) events. The receptor for advanced glycation end products (RAGE) has been implicated in the perpetuation of the chronic inflammatory response in vascular disease. A Gly82→Ser polymorphism in the RAGE gene, which is associated with enhanced RAGE signaling, is present more frequently in patients with RA than the general population. To investigate whether RAGE Gly82→Ser polymorphism is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Functional polymorphisms in the AGER gene that encodes RAGE are associated with rheumatoid arthritis [24,25], and it was recently reported that sRAGE levels were strongly associated with carriage of the rheumatoid arthritis-associated RAGE 82S polymorphism [24]. Large community-based, genome-wide association studies have recently reported that single nucleotide polymorphisms in the AGER gene are associated with a reduced FEV1/FVC ratio indicative of airflow obstruction [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Functional polymorphisms in the AGER gene that encodes RAGE are associated with rheumatoid arthritis [24,25], and it was recently reported that sRAGE levels were strongly associated with carriage of the rheumatoid arthritis-associated RAGE 82S polymorphism [24]. Large community-based, genome-wide association studies have recently reported that single nucleotide polymorphisms in the AGER gene are associated with a reduced FEV1/FVC ratio indicative of airflow obstruction [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…MMP-1 polymorphism has been implicated in OA in a Turkish population, and RAGE polymorphism has been implicated in rheumatoid arthritis (RA) in Caucasians (Carroll et al, 2007;Barlas et al, 2009). However, no studies have analyzed the association between RAGE, S100A8, and MMP-1 single-nucleotide polymorphisms (SNPs) and OA in the Han Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…The original cohort consisted of 231 RA patients [251], of whom serum KYN concentration levels were measured in 129. The follow-up characteristics of the cohort are in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This cohort has been previously described [251]. This cohort was followed for 10 years within this hospital clinic setting.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation